Rethinking Food Markets Initiative: Stakeholders Workshop in Nigeria - Onilogbo, Omobolanle (CGIAR System Organization, 2023)
The CGIAR Initiative on ‘Rethinking Food Markets' led by the International Food Policy Research Institute (IFPRI), organized a two-day (12-13 Dec. 2022) stakeholders workshop in Abuja, Nigeria. The workshop aims to engage with key stakeholders to kick-start the co-designing of innovations and interventions in ‘Food Markets and Value Chains’ to enhance employment opportunities and increase income for smallholders and SMEs along the agri-food value chains in Nigeria. Specifically, the workshop’s objectives are: (1) to introduce the initiative to policymakers, implementing partners, and scaling stakeholders in Nigeria; (2) to share the findings from the Scoping Study in Nigeria with stakeholders and validate the results; (3) to co-identify and co-design innovations and interventions with partners for piloting in Nigeria; and (4) to kick-start bundling of innovations/interventions and learning between the different work packages within the Initiative.